Kajian Psikologis Mengenai Komunikasi Berbasis Paperless Office - Ramdhani, Neila (Jurnal Psikologi, 2011)
Paperless Office or PLO was created to facilitate work demands, which strongly requires speed, accuracy and also relates with issues concerning paper use reduction in several organizations in theworld. In the Faculty of Psychology UGM, PLO has already been used since 2009. Has this particular technology actually fulfilled the aforementioned expectations above? If it has, then whattypes of issues are well discussed through this system? Are there issues that are difficult to discuss using this system? Why is that so? This study aims to describe use of PLO systems among staffs inthe Faculty of Psychology UGM. Both quantitative and qualitative methods are applied in the study. Quantitative method was conducted using descriptive technique towards the PLO database followed by the categorization of the users, discussed topics that support daily office work, as well as the completeness and order of topics that are discussed. Following the categorization of users, datacollection was further carried out by interviewing faculty members to explore reasons for not using the system. Other issues that are to be studied include the fluent exchange of information for each ofthe discussed topics based from the categorization process. Content analysis is performed towards the data obtained from this interview. The results of the analysis demonstrate that PLO usage reaches84%. Topics most interestingly discussed concern social topics, for example news of an ill member, birth of a baby, and promotion. The topic least responded to, related with academic careeropportunities. The percentage of PLO usage provides a description related to the cultural issues that hold importance in innovation diffusion in office work.